Assyrian Chronology and Ideology of Kingship: The Impact on Biblical Historiography and Religion - Derstine, Philip (Religions, 2024)
Studies since 2005 have raised doubts about the Assyrian King List’s (AKL) intention and ability to measure absolute time. If telescoping of time occurred, it would be difficult to detect during periods when royal annals were scant. The best way to detect discontinuity in the AKL is by comparison with contemporary king lists, such as one constructed from 1–2 Kings regnal formulas. If the AKL conflates time, an assessment of the plausibility of historical scenarios resulting from different timeframes allows for discrimination between one timeline or another. Israel and Judah’s interlocking chronological systems make a comparison with the Neo-Assyrian timeline possible but contain 44 more years than the timeline implied by the AKL and Assyrian Eponym Canon. By narrowing the window of time within which a deficit in the Neo-Assyrian canons may have occurred, possible reasons for missing years in the consensus chronology present themselves. This investigation concludes that Assyria sought to maintain the legitimacy of the institution of kingship during a protracted period of unacceptable or anomalous authority. Concerns surrounding the continuity of kingship would have dictated the final form of the Assyrian King List/Assyrian Eponym Canon. Using Divided Kingdom regnal data, a revision of the historical timeline is proposed that aligns archaeological, radiocarbon, biblical, and Assyrian data.